KARAKTERISTIK, PERSEPSI, DAN TINGKAT KEPUASAN WISATAWAN TERHADAP PELAYANAN, FASILITAS, DAN AKSESIBILITAS DI DESTINASI WISATA KOLAM RENANG AIR SANIH - Avrilla Sekar Pahlevi Utami; Putu Indra Christiawan; I Gede Budiarta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify tourist characteristics and analyze tourists' perceptions of accessibility, service quality, facilities, and overall satisfaction at Air Sanih Swimming Pool Tourist Destination, Buleleng Regency, Bali. The study employed a mixed-methods approach using an explanatory sequential design. Quantitative data were collected through a questionnaire based on the Service Quality (SERVQUAL) model, while qualitative data were obtained through interviews, observations, and documentation. Quantitative data were analyzed descriptively using the SERVQUAL approach and further enriched through thematic analysis of the qualitative findings. The results indicate that tourists generally perceive the destination's accessibility as good, although the availability of public transportation remains limited. The quality of services provided by the management was also rated positively; however, improvements are still needed to ensure consistent service delivery. Existing facilities were considered adequate to meet visitors' needs, but the capacity and comfort of several supporting facilities require improvement, particularly during peak visitor periods. Overall, tourist satisfaction was categorized as good, although several indicators have not yet reached an optimal level. The study concludes that integrated improvements in accessibility, service quality, and facilities are essential to enhance tourist satisfaction and support the sustainable development of the Air Sanih Swimming Pool Tourist Destination.